DAKWAH PADA MASYARAKAT PEDESAAN DALAM BINGKAI PSIKOLOGI DAN STRATEGI DAKWAH - Ansori hidayat (Jurnal Bimbingan Penyuluhan Islam, 2019)
Society is a group of people who live together in an area and form a region and form a system, both semi-closed, where the contractions that occur in it are individuals who are in the group. Psychology is the science that studies or investigates human or animal behavior as seen by birth. The flow of behaviorism focuses its attention on outward behavior, because it is considered as a description of inner feelings or the soul. While the flow of sociology defines psychology as science that studies the process of human adaptation to the natural surroundings of Da'wah that can be done in rural communities, namely the first, with the wisdom method, which is clear speech and is accompanied by propositions that reinforce the truth and eliminate doubts. Second, the oral method is a method through oral which is done in a way such as lectures, sermons, and others. Third, using the method of preaching is billati hiya ahsan is an approach that instills mutual respect between dai and mad'u. Fourth, by using the bil-hal method, it is da'wah with real deeds where the da'wah activities are carried out through role models and real charitable actions